Neuro-Ophthalmic Visual Impairment in the Setting of COVID-19 - Dinkin, Marc; Sathi, Swetha (Seminars in Neurology, 2023)
We set out to describe in detail the afferent neuro-ophthalmological complications that have been reported in association with coronavirus disease 2019 (COVID-19) infection. We describe and elaborate on mechanisms of disease, including para-infectious inflammation, hypercoagulability, endothelial damage, and direct neurotropic viral invasion. Despite global vaccination programs, new variants of COVID-19 continue to pose an international threat, and patients with rare neuro-ophthalmic complications are likely to continue to present for care.Afferent complications from COVID-19 include homonymous visual field loss, with or without higher cortical visual syndromes, resulting from stroke, intracerebral hemorrhage, or posterior reversible leukoencephalopathy. Optic neuritis has frequently been reported, sometimes along with acute disseminated encephalomyelopathy, often in association with either myelin oligodendrocyte glycoprotein antibodies (MOG-IgG) or less commonly aquaporin-4 seropositivity or in newly diagnosed multiple sclerosis. Ischemic optic neuropathy has rarely been reported. Papilledema, resulting either from venous sinus thrombosis or idiopathic intracranial hypertension in the setting of COVID-19, has also been described.Observed afferent neuro-ophthalmic associations need to be confirmed though larger comparative studies. Meanwhile, the range of possible complications should be recognized by neurologists and ophthalmologists alike, to facilitate faster diagnosis and treatment of both COVID-19 and its neuro-ophthalmic manifestations.
Keywords: COVID-19; optic neuritis; cranial; stroke